ANALISIS PERMINTAAN BERAS DI KOTA SAMARINDA (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
The purpose of this research is to analyze the effect of Price and Income per Capita to Rice Demand in Samarinda City. This research uses library research. The used data type is quantitative data. The data source for this research is secondary data. The data is collected by collecting data to related instance and analyzed using function powers model Cobb-Douglas. This researchs result shows that Rice Price and Income per Capita has a significant effect to Rice Demand in Samarinda City. Calculation result correlation coefficient (R= 0,984) which means that free variable has a strong bond. When value of R2 is 0,968 which shows that free variable in this research can explain that bound variable as big as 96,8% while the rest is explained by other variable.Keyword: Price, Income per Capita, and Rice Demand.